2014
DOI: 10.1590/1516-4446-2013-1243
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor performance in euthymic bipolar disorder: the MPraxis (PennCNP) analysis

Abstract: Background: Sensorimotor deficits are an important phenomenological facet observed in patients with bipolar disorder (BD). However, there is little research on this topic. We hypothesize that the MPraxis test can be used to screen for motor impairments in BD aiming movements. Method: The MPraxis, which is a quick and easy-to-apply computerized test, measures sensorimotor control. During the test, the participant must move the computer mouse cursor over an ever-shrinking green box and click on it once. We predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Participants were instructed to click on squares that appear randomly on the screen, with each successive square smaller and thus more difficult to track. The test depends upon function of visual and sensorimotor cortices ( Gur et al, 2001 ; Gur et al, 2010 ; Neves et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were instructed to click on squares that appear randomly on the screen, with each successive square smaller and thus more difficult to track. The test depends upon function of visual and sensorimotor cortices ( Gur et al, 2001 ; Gur et al, 2010 ; Neves et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…The current implementation uses 20 consecutive stimuli. As a screener for computer skill, the MP has been included in every implementation of the CNB and validated for sensitivity to age effects (18), sex-differences (40), and associations with psychopathology (33). …”
Section: Methodsmentioning
confidence: 99%
“…In addition to mood changes, patients with BD tend to show deficits in executive functions, verbal and visuospatial episodic memory, working memory (WM), verbal learning, information processing speed, sustained attention, and sensorimotor performance (Bora et al, 2009; Latalova et al, 2011; Lage et al, 2013; Loschiavo et al, 2013; Lee et al, 2014; Neves et al, 2014). Some studies have suggested more severe cognitive deficits in episodes of manic/mixed mood compared with depressive and euthymic episodes (Sweeney et al, 2000).…”
Section: Introductionmentioning
confidence: 99%